2013
DOI: 10.1053/j.gastro.2013.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Signaling Regulates Differentiation and Maintenance in the Exocrine Pancreas

Abstract: BACKGROUND & AIMS The Hippo signaling pathway is a context-dependent regulator of cell proliferation, differentiation, and apoptosis in species ranging from Drosophila to humans. In this study, we investigated the role of the core Hippo kinases—Mst1 and Mst2—in pancreatic development and homeostasis. METHODS We used a Cre/LoxP system to create mice with pancreas-specific disruptions in Mst1 and Mst2 (Pdx1-Cre;Mst1−/−;Mst2fl/fl mice), the mammalian orthologs of Drosophila Hippo. We used a transgenic approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(167 citation statements)
references
References 23 publications
6
159
0
2
Order By: Relevance
“…Modulation of Hippo signaling has frequently been reported to result in alterations of Notch target gene expression. For example, genetic deletion of Mst1/2 in pancreatic epithelium resulted in increased Yap expression and a robust increase in Hes1 expression (Gao et al, 2013). Yap overexpression in hepatocytes caused upregulation of Notch1/2, Jagged1, Hes1 and the Notch target Sox9 (Yimlamai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulation of Hippo signaling has frequently been reported to result in alterations of Notch target gene expression. For example, genetic deletion of Mst1/2 in pancreatic epithelium resulted in increased Yap expression and a robust increase in Hes1 expression (Gao et al, 2013). Yap overexpression in hepatocytes caused upregulation of Notch1/2, Jagged1, Hes1 and the Notch target Sox9 (Yimlamai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given the diversity and breadth of cellular contexts in which Notch and Hippo signaling function in development and disease, it is not surprising that these two signaling pathways frequently intersect Heallen et al, 2011;von Gise et al, 2012;Afelik and Jensen, 2013;Gao et al, 2013;Li et al, 2009;Makita et al, 2008). For example, hepatocyte-specific Yap overexpression leads to an upregulation of Notch1, Notch2, Jagged1 (Jag1) and the Notch target gene Hes1 (Yimlamai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that changes in YAP localization are essential for proper pancreas development (Gao et al, 2013;George et al, 2012). Analyses of pancreas-specific Mst1/2 knockout mice have revealed severe developmental defects that correlate with increased nuclear hypophosphorylated YAP (Gao et al, 2013;George et al, 2012).…”
Section: Pancreasmentioning
confidence: 99%
“…[76][77][78] The involvement of the Hippo/MST2 pathway in epithelial behavior and downstream processes were recently reviewed. 79 MST2 itself and its closest isoform MST1 were shown to be crucial for 1,25-dihydroxyvitamin D 3 -mediated monocytic differentiation of myeloid leukemia HL60 cells, 42 control the downstream kinase YAP to control pancreatic acinar differentiation mice, 80 regulate trophoblast differentiation via the transcription factor Mash2 in the placenta, 81 and are required for embryonic stem cell differentiation. 82 In addition, MST1/2 play a role in differentiation of hematopoietc and endothelial progenitor cells in Xenopus, 83 and MST1 was identified as a crucial caspase-3 effector in myoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%